Control Module of Trans-esterification Reactor of a Biodiesel Plant - Hawley, Christopher; Sen, Tushar (HPC Publishers Distributors Pvt. Ltd., 2010)
This paper presents the design of an effective control system around an esterification reactor of a biodiesel plant. The control system developed aims to maintain the desired operating temperature, level and of most significance the reaction extent in the reactor. The progress and endpoint of the transesterification reaction can successfully be monitored online using in-situ viscosity measurements. This technology eliminates the requirement of offline compositional analysis through gas chromatography. Reaction time is the controlling factor in determining the yield of esters. Thus, employing a fast acting 'composition' analysis technique provides plant management and operators with more reliable, robust control. The reaction extent in this work was achieved by using the viscosity as an on line measurement allowing for inferred online control of product composition. The control configuration, methodology used, dynamic model development, tuning of the control loops and analysis of control philosophy ore presented in this paper. Determining the control configuration and tuning of the control loops are based on developing mathematical models of the process dynamics and its instrumentation and applying the correct controller mathematics into the "loop", formed between the process and its equipment, in order to achieve the desired dynamic behaviour and control of the reactor.